Síntese, caracterização e estudos biológicos de complexos de cobre(II) contendo derivados dos ácidos picolínico e nicotínico - Almeida, Janaína do Couto (2019)
Since the discovery of cisplatin antitumor properties, several platinum-based complexes have been developed as new chemotherapeutic agents. Although they are widely used to treat various types of cancer, there are still limitations due to serious side effects and the intrinsic or acquired cellular resistance. Due to these disadvantages, one of the alternatives is the development of potential antitumor agents based on metals found naturally in the body, such as copper. Thus, this work describes the synthesis and characterization of copper(II) complexes with hydroxypyridinecarboxylic acids and N,N-donor ligands as potential antitumor and antimicobacterial agents. Complexes of the type [Cu(L-L)(N-N)ClO4] and [Cu(L-L)2], where L-L = 3-hydroxypicolinic acid (3-HPA), quinaldic acid (QNA), 2- hydroxynicotinic acid (2-HNA), 2-mercaptonicotinic acid (2-MNA) ou 6-hydroxynicotinic acid (6-HNA) and N-N = 2,2-bipyridine or 1,10-phenanthroline were characterized by elemental analysis, conductivitymeasurements, infrared spectroscopy (FT-IR), ultravioletvisible spectroscopy (UV-Vis), electronic paramagnetic resonance (EPR) and high-resolution electrospray ionization mass spectrometry (HRESIMS). The results indicate that the 3-HPA and QNA ligands coordinate to the copper(II) ion in a bidentate manner via nitrogen and oxygen atoms of the carboxylate. In turn, the 2-HNA, 2-MNA and 6-HNA ligands coordinates via oxygen atom of carboxylate and oxygen atom of carbonyl, sulfur and oxygen atom of the carboxylate, respectively. For copper complexes of type [Cu(L-L)(N-N)ClO4], the molar conductivity values of 10−3 M solutions are in the range of 1:1 electrolytes, this indicates the labilization of the axial ligands in solution (perchlorate anion) resulting in species of the type [Cu(L-L)(N-N)]+. To ascertain their pharmacological potential, the cytotoxic activity of the compounds was investigated in three tumor cell lines (A549, K562, MDA-MB-231) and two normal cell lines (MRC-5, MCF-10A). For the K562 cell line, the [Cu(3-HPA)(phen)ClO4] and [Cu(QNA)(phen)ClO4] complexes with 1,10-phenanthroline exhibited good cytotoxic activity with IC50 values of 2.3 and 2.1 μM, respectively, being more active than carboplatin (10 μM) and free ligands. In relation to the MDA-MB-231 cell line, the [Cu(QNA)(phen)ClO4], [Cu(2-HNA)(phen)ClO4], [Cu(2-MNA)(phen)ClO4], [Cu(6- HNA)(phen)ClO4] and [Cu(6-HNA)(bipy)ClO4] complexes were more active than carboplatin (> 100 μM) and free ligands. The [Cu(QNA)(phen)ClO4], [Cu(2-HNA)(phen)ClO4], [Cu(2- MNA)(phen)ClO4] and [Cu(6-HNA)(phen)ClO4] complexes bind to ct-DNA with Kb values in the range of 103 M−1. According to data from circular dichroism (CD) and fluorescence spectroscopy the complexes appear to bind to the DNA groove. The antituberculose activity of twelve complexes was also evaluated against the sensitive strain MTB H37Rv and the [Cu(QNA)(phen)ClO4], [Cu(2-HNA)(phen)ClO4] and [Cu(2-MNA)(phen)ClO4] complexes showed good activity with MIC values inferior than 2.7 μg mL−1, values lower than those found for the respective free ligands. Thus, the synthesized complexes showed good cytotoxic and antimicobacterial activity and are promising candidates for further studies.